2016
DOI: 10.1038/srep24927
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomics and Transcriptomics Analysis Reveals Potential Mechanisms for Favorable Prognosis of Patients with HPV-Positive Head and Neck Carcinomas

Abstract: Patients with HPV-positive head neck squamous cell carcinomas (HNSCC) usually have a better prognosis than the HPV-negative cases while the underlying mechanism remains far from being well understood. We investigated this issue by an integrative analysis of clinically-annotated multi-omics HNSCC data released by the Cancer Genome Atlas. As confirmatory results, we found: (1) Co-occurrence of mutant TP53 and HPV infection was rare; (2) Regardless of HPV status, HNSCCs of wild-type TP53 implied a good survival c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Studies implementing and exploring integrative approaches have unveiled therapy candidates in many tumors 26 , 28 . Nevertheless, molecular mechanisms underlying penile cancer remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies implementing and exploring integrative approaches have unveiled therapy candidates in many tumors 26 , 28 . Nevertheless, molecular mechanisms underlying penile cancer remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, by assessing 23 PeCa patients we identified a high sensitivity and specificity of PPARG , MMP1 and MMP12 and hsa-miR-31-5p, hsa-miR-223-3p and hsa-miR-224-5p to distinguish penile tumors from normal tissue 22 . Next generation sequencing studies in penile carcinomas revealed the involvement of well-described genes, such as EGFR , PIK3CA , TP53 and CCND1 23 25 and dysregulated miRNAs 26 , all associated with cancer signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck cancers with wild-type TP53 have a better prognosis than those with TP53 mutations [ 2 , 83 ]. HPV positivity and p16 INK4A expression, which are both related to retention of wild type TP53 , are also positively correlated with overall 3-year survival in anal cancers [ 84 ].…”
Section: Genes and Pathwaysmentioning
confidence: 99%
“…Another point of emphasis derived from the present overview is the growing integration among omics data obtained on the same cohort of patients. Even if these experiences are still limited for HNSCC and in terms of types of omics employed and amount of published studies [23,27,43,58,66,76], these initiatives enabling to better dissect cancer complexity deserve further investigations. Moreover, we can expect that new approaches based on artificial intelligence will be available in the next future dealing with more complex data even integrating multi-omics layers [94].…”
Section: Discussionmentioning
confidence: 99%